Positive Molecular Detection of Rickettsia helvetica in Great Tits From Central Poland - Jarosław Wawrzyniak; Joanna Strzelczyk; Cecilia Panek; Michał Glądalski; Adam Kaliński; Marcin Markowski; Joanna Skwarska; Piotr Zieliński; Jerzy Bańbura (Ecology and Evolution, 2025)
ABSTRACT Ticks spread to new habitats via wild mammals and birds, with urban green spaces potentially colonized through bird transportation. Rickettsia is a genus of bacteria that can cause diseases in humans and animals, which is often transmitted by ticks. This study investigated the presence of Rickettsia in the great tit (Parus major), a widespread Eurasian passerine bird, and in ticks attached to them. Samples were collected in three locations around Lodz, Poland: a suburban forest, an urban park, and green patches near the city center. Using Nested PCR (polymerase chain reaction), 73 samples of blood from birds and five ticks taken from great tits (attached to them) were tested for the presence of Rickettsia DNA. Six birds (8.2%) tested positive for Rickettsia spp., with detections across all locations. Sequencing confirmed the presence of Rickettsia helvetica, a known zoonotic species. None of the ticks tested positive for Rickettsia. These findings indicate that synanthropic bird species, like the great tit, may play a role in spreading Rickettsia bacteria into urban areas. This study highlights the potential importance of birds in the ecology of tick‐borne diseases in urbanized environments.